2019
DOI: 10.1089/end.2018.0869
|View full text |Cite
|
Sign up to set email alerts
|

Does Glomerular Filtration Rate at Discharge After Partial Nephrectomy Predict Long-Term Glomerular Filtration Rate Stability?

Abstract: Introduction: Being able to predict glomerular filtration rate (GFR) plateau after partial nephrectomy (Pnx) is an important goal in providing patients with a confident projection of maintained renal function. As such, in an ethnically and socioeconomically diverse, inner city cohort of patients undergoing Pnx, we compared preoperative (pre-op) and day of discharge (DC) GFR to that of long-term GFR measured at 12-18 months to evaluate postoperative (post-op) GFR stability. Methods: A total of 162 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Owing to intraoperative ischemic injury and excision of the renal parenchymal unit, renal function may decrease following PN. Recent mechanistic studies have revealed that acute kidney injury after PN may contribute to chronic kidney disease development and increase the risk of cardiovascular disease (3,4). A number of studies into the predictors of renal function after PN have been conducted, and determinants associated with immediate or late renal function after PN have been well established (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to intraoperative ischemic injury and excision of the renal parenchymal unit, renal function may decrease following PN. Recent mechanistic studies have revealed that acute kidney injury after PN may contribute to chronic kidney disease development and increase the risk of cardiovascular disease (3,4). A number of studies into the predictors of renal function after PN have been conducted, and determinants associated with immediate or late renal function after PN have been well established (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%